Calculation of stresses on shallow penetrometers and footings. - Houlsby, G; Wroth, C (Graham and Trotman, London; IHRDC, Boston, 1984)
A short review is made of the types of analyses available for cone penetration tests. The assumptions involved in analyses using the method of characteristics (slip line methods) are discussed, and some analyses of problems of shallow cone penetration and bearing capacity are presented. Graphical results are presented for the variation of the cone factor, Nc, with the angle and roughness of a shallowly penetrating cone. The second example of the application of the method is to problems of bearing capacity on soils with strength increasing with depth, and is relevant to the design of very large concrete gravity oil-production platforms. Numerical values of bearing capacity factors for smooth and rough circular footings on non-homogeneous soils are presented and compared with the equivalent values for strip footings.-from Authors